Flood Inundation Mapping in Medan Maimun, Medan City Using HEC-RAS 2D and the Nakayasu Synthetic Unit Hydrograph - Sarra Rahmadani; Dewi Fitria Marlisa; Rumilla Harahap; Siti Zulfa Yuzni; Nanda Savira Ersa; Cut Meuthia Rani; Al Fatahillah; Muh. Ilham Anggamulia; Yusuf Aulia Lubis; Anni Zahara Putri; Wisnu Prayogo (International Journal of Hydrological and Environmental for Sustainability, 2026)
Flood inundation mapping is a critical tool for urban flood risk assessment in tropical cities. This study investigates flood inundation extent in Medan Maimun Sub-district, Medan City, one of the most flood-prone areas in North Sumatra, Indonesia, where flood depths of approximately 3 meters were reported in February 2022 and December 2023. The study aims to: (1) determine design rainfall through frequency analysis and calculate design flood discharge for return periods of 2, 5, 10, 25, 50, and 100 years using the Nakayasu Synthetic Unit Hydrograph (SUH Nakayasu) method; (2) simulate flood routing using two-dimensional hydraulic modeling; and (3) map the resulting flood inundation extent for each return period. Rainfall frequency analysis used annual maximum rainfall data from two stations for the period 2014–2023, with the Log Pearson III method selected based on Chi-Square goodness-of-fit testing. Design flood discharges ranged from 383.403 m³/s at the 2-year return period to 555.149 m³/s at the 100-year return period. Flood routing and inundation mapping were performed using HEC-RAS version 5.0.7 integrated with RAS Mapper. Total inundation area increased from 110.982 ha at the 2-year return period to 126.581 ha at the 100-year return period, covering approximately 41.6% of the sub-district area at the 100-year return period. The model was not formally calibrated or validated against observed flood data; results should be interpreted as indicative of relative flood risk patterns rather than precise predictions. The flood inundation maps produced provide a useful scientific basis for flood mitigation planning in Medan city, Indonesia.